Take away or delivery? acceptance of online food delivery (OFD) during COVID-19 pandemic/ Nur Hafizah Muhammad and Nur Dalila Mat Yusoff - Muhammad, Nur Hafizah; Mat Yusoff, Nur Dalila (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
There has been a rise in the use of online food delivery applications, especially at this time of the COVID19 pandemic. Research has shown a few important factors that influence the public in using online food delivery applications. This study aims to determine the three main determinants that influence the acceptance of online food delivery applications. Hence, to gather data, an online questionnaire has been distributed through an online platform. A non-linear regression analysis was performed to explain the determinants, along with a descriptive analysis to answer the objective of the study. A total of 291 participants responded to the survey and the outcomes showed that performance expectancy, social influence, and perceived trust have a significant relationship with consumers' acceptance of online food delivery applications. Overall, in Malaysia, the majority of the online food delivery application users prioritised both performance expectation and perceived trust more than social influence.